Writing a technical note - Ng, K.H.; Peh, W.C.G. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2010)
A technical note is a short article giving a brief description of a specific development, technique or procedure, or it may describe a modification of an existing technique, procedure or device applicable to medicine. The technique, procedure or device described should have practical value and should contribute to clinical diagnosis or management. It could also present a software tool, or an experimental or computational method. Technical notes are variously referred to as technical innovations or technical developments. The main criteria for publication will be the novelty of concepts involved, the validity of the technique and its potential for clinical applications.